Performance Analysis of Peanut Shelling Machine Against Peanut Pod Diameter Using Electric Motor Drive - Ferdiansyah, Imam; Wiryono, Budy; Karyanik, Karyanik (Universitas Muhammadiyah Mataram, 2022)
Groundnut production in West Nusa Tenggara Province has increased every year. Post-harvest handling of peanuts at the farm level is generally still done traditionally, especially when harvesting, threshing pods or stripping the peel, which requires a lot of labour. This study aims to determine the effect of peanut pod diameter on each parameter, tool efficiency, and tool production quality. The method used in this research is the experimental method by conducting experiments directly in the laboratory. The parameters observed in this study are the efficiency of the tool, the need for electrical power, and the quality of peanut seed stripping. The analysis results showed that each treatment with different diameters had no significant effect on each parameter observed. The stripping quality of the three treatments has not met the standard.